Post-veraison regulated deficit irrigation in 'Crimson Seedless' tablegrape saves water and improves berry skin color - Pinillos, Virginia; Chiamolera, Fernando M. [UNESP]; Ortiz, Juan F.; Hueso, Juan J.; Cuevas, Julián (Elsevier, 2015)
Poor skin color in red table grape cultivars is one of the most troublesome difficulty producers facein the management of this crop. Recent EU limitations of ethylene release products left growers withpoor prospects to improve the color of the berry. In this work, we have explored 'Crimson Seedless'response to deficit irrigation from veraison to the end of harvest and we observed an improvement inthe development of the berry skin color. Earlier yield was also obtained in plants under deficit irrigation,with a higher percentage of yield in the first picking operations, due to earlier acquisition of color by theberries. Negative effects on berry size or on total yield were not observed. Therefore, we may recommenddeficit irrigation from veraison to harvest as a mean to increase the quality of the berry and to reducewater consumption.
Keywords: Berry size; Fruit earlinessa; Vitis vinifera; Water stress; Yield